Pengaruh Gaya Belajar dan Budaya Literasi Terhadap Hasil Belajar Siswa Setingkat SD - Sholicha, Nikmatus; Afifah, Laela Nur; Darmawan, Didit (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the influence of learning styles and literacy culture on student learning outcomes at the elementary school level. The method used is a library search, by collecting and reviewing various secondary data sources, such as scientific literature, research journals, and academic articles relevant to the topic. The data analysis technique used is content analysis, namely by reviewing the content of various sources to understand the relationship between learning style approaches, the implementation of literacy culture, and student learning outcomes. Educational success in elementary schools is influenced by various factors, including learning styles and literacy culture. Learning styles include visual, auditory, and kinesthetic approaches that help students absorb information, while literacy culture involves reading habits and critical thinking skills that contribute to learning outcomes. However, low interest in reading and a lack of attention to individual learning styles are major obstacles to improving the quality of education. The results of the analysis show that students whose learning styles are accommodated in the learning process have better learning outcomes. In addition, the implementation of literacy culture through the School Literacy Movement (GLS) program has been proven effective in improving students' reading skills, learning interest, and understanding of the material. This study emphasizes the importance of the role of teachers in understanding students' learning styles and integrating literacy activities to support educational success.